THEORETICAL AND EXPERIMENTAL STUDIES OF ENERGY-EFFICIENT GRINDING PROCESS OF CEMENT CLINKER IN A BALL MILL - Kuznetsova M.M.; Ved V.E. (Problems of the Regional Energetics, 2014)
The article presents results of theoretical and experimental research of grinding process of bulk materials in a ball mill. The new method of determination of energy efficiently mode of operation of ball mills in a process of a cement clinker grinding is proposed and experimentally tested.